Comparison between two Polyethersulfone concentrations in hollow fiber ultrafiltration membranes. Is it worth to use more polymer? - Gonzaga, Karen; Mierzwa, Jose Carlos (Eclética Química, 2021)
Polyethersulfone (PES) hollow fiber membranes were fabricated using dry-jet wet spinning technique, a phase inversion method, with 16 and 20% PES, N-methyl-2-pyrrolidone (NMP) as solvent and tap water as nonsolvent, in order to evaluate if the amount of polymer has a significant effect on its properties. They were characterized using SEM for a morphological analysis, a continuous system to measure pure water permeability (PWP) and molecular weight cutoff (MWCO), and a universal testing machine to tensile tests. The obtained results for PWP was an average of about 220 L m- ² h-1 bar-1 for the 16% PES membrane and 174 L m- ² h-1 bar-1 for the 20% PES membrane. The results of mechanical resistance and MWCO did not present statistical differences. Thus, it is confirmed that the 16% PES membrane can be as good as the 20%, despite using less polymer, a finding that can further motivate membrane modification studies and other related works.